2012
DOI: 10.1038/nature11240
|View full text |Cite
|
Sign up to set email alerts
|

Programmed elimination of cells by caspase-independent cell extrusion in C. elegans

Abstract: The elimination of unnecessary or defective cells from metazoans occurs during normal development and tissue homeostasis as well as in response to infection or cellular damage1. While many cells are removed through caspase-mediated apoptosis followed by phagocytosis by engulfing cells2, other mechanisms of cell elimination occur3, including the extrusion of cells from epithelia via a poorly understood, possibly caspase-independent process4. Here we identify a mechanism of cell extrusion that is caspase-indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
104
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(113 citation statements)
references
References 38 publications
9
104
0
Order By: Relevance
“…A recent report showed that PIG-1, PAR-4, STRD-1, and two of the MOP25 homologs affect several caspase-independent cell deaths (Denning et al 2012) (see Discussion), further supporting our hypothesis that these genes act together in the same pathway.…”
Section: Par-4 and Strd-1 Function In The Same Pathway As Pig-1 And Psupporting
confidence: 76%
See 1 more Smart Citation
“…A recent report showed that PIG-1, PAR-4, STRD-1, and two of the MOP25 homologs affect several caspase-independent cell deaths (Denning et al 2012) (see Discussion), further supporting our hypothesis that these genes act together in the same pathway.…”
Section: Par-4 and Strd-1 Function In The Same Pathway As Pig-1 And Psupporting
confidence: 76%
“…For example, we showed that pig-1 and strd-1 regulate the PLM lineage ( Figure 3B), suggesting that these genetic interactions are not specific for the Q.p lineage. Moreover, Denning et al (2012) recently reported that pig-1, par-4, and strd-1 act together to regulate the death of a subset of cells that die early in the C. elegans embryo. These cells die by a caspase-independent mechanism and are shed from the embryo in caspase-deficient mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Denning et al [8] went further to find the regulators of the death, which is conferred by shedding. Again the information provided by the invariant developmental lineage, and the ability to study development at the cellular level came to their aide.…”
mentioning
confidence: 99%
“…A recent Nature paper by Denning et al [8] describes a novel form of developmentally regulated programed cell death in C. elegans. This cell death, which the authors refer to as cell shedding, is independent of the CED-3 caspase as well as of the three further caspases encoded in the C. elegans genome.…”
mentioning
confidence: 99%
“…C. elegans harbors only one ortholog of Xk proteins, CED-8, known to participate in the phagocytic removal of apoptotic corpses [6]. To determine the role of CED-8 in PS exposure, the authors took advantage of the "floater" assay, which is based on the appearance of floating cells ("floaters") that have detached from developing C. elegans embryos defective for apoptotic cell phagocytosis [7]. Nagata's group discovered that ced-8 deficiency leads to the accumulation of floaters.…”
mentioning
confidence: 99%